2004
DOI: 10.1097/01.smj.0000082003.98003.88
|View full text |Cite
|
Sign up to set email alerts
|

Pernicious Anemia: Presentations Mimicking Acute Leukemia

Abstract: Vitamin B12 deficiency can cause profound alterations in the bone marrow. These alterations can mimic the more serious diagnosis of acute leukemia. The two patients described in this report were originally suspected of having acute leukemia or myelodysplasia on the basis of the bone marrow smear, and induction chemotherapy was considered. However, after further studies, they were both found to have vitamin B12 deficiency, and parenteral vitamin B12 administration resulted in normalization of the bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 4 publications
2
15
0
1
Order By: Relevance
“…Aitelli et al had stated that Vitamin B12 deficiency can cause profound alterations in the bone marrow and may mimic acute leukaemia or myelodysplasia. 23 However, after further studies, they were both found to have vitamin B 12 deficiency, and parenteral vitamin B 12 administration resulted in normalization of the bone marrow. So, a trial of Vitamin B 12 and folic acid therapy should be given before labelling a case as myelodysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Aitelli et al had stated that Vitamin B12 deficiency can cause profound alterations in the bone marrow and may mimic acute leukaemia or myelodysplasia. 23 However, after further studies, they were both found to have vitamin B 12 deficiency, and parenteral vitamin B 12 administration resulted in normalization of the bone marrow. So, a trial of Vitamin B 12 and folic acid therapy should be given before labelling a case as myelodysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Megaloblastic anaemia which is due to impaired DNA synthesis is considered as panmyelosis and may progress to pancytopenia (Carmel, 2009). Megaloblastic anaemia presenting with pancytopenia may clinically mimic or simulate pancytopenia arising due to other causes including leukaemia (Aitelli, Wasson & Page, 2004). Bone marrow aspiration/trephine biopsy along with relevant laboratory investigations are generally required to distinguish such cases.…”
Section: Introductionmentioning
confidence: 99%
“…The BM of patients with MBA can display significant atypical features (e.g. hypercellularity, erythroid hyperplasia, increased nuclear to cytoplasmic ratios, and increased mitotic figures), 24 which may mislead the diagnostician into considering a neoplastic process 25 . Therefore, we would suggest excluding MBA before considering non‐acute myeloid neoplastic categories (i.e.…”
Section: Discussionmentioning
confidence: 99%